MORTALITY OF BLACK-BAND MYLEUS Myloplus Schomburgkii DUE TO POOR WATER QUALITY ASSOCIATED WITH OVERPOPULATION OF DUCKWEEDS IN A CULTURE POND IN THE PERUVIAN AMAZONIA - MURRIETA-MOREY, Germán Augusto (2021)
Ponds covered with duckweeds release nutrients rapidly, causing problems of eutrophication of the water which can reduce water clarity and quality, creating a hypoxic or anoxic ‘dead zone' lacking sufficient oxygen to support most organisms. In the present study, the sudden mortality of black-band myleus Myloplus schomburgkii Jardine, 1841 drove the investigate of factors that caused the death of the specimens registered in a fish pond in the Peruvian Amazon. After the tallying of dead fish, it was revealed that sixty individuals (75% of the total population) of M. schomburgkii had died. The taxonomic identification of the aquatic plant revealed the presence of “duckweeds” locally named in Peru as “lenteja de agua” Lemna minor distributed throughout the pond. Physical and chemical water parameters revealed low levels of oxygen, acid water, and high levels of nitrate and phosphate. Since duckweeds cannot be completely eliminated from waters that are conducive to its growth and require periodic harvesting to prevent matting, proper management strategies therefore become critical to guarantee good quality of water in the pond and avoid black-band myleus deaths due to imbalances in physical and chemical parameters.